Final Semester Assessment (PAS) in The Covid-19 Era Based on the Integrity of Teachers, Students, and Parents - Sari, Eva Dwi Kumala; Lisnawati, Santi; Ananthia, Winti (Jurnal Pendidikan Indonesia, 2021)
This study aims to analyze the integrity of teachers, students, and parents in the Final Semester Assessment (PAS) conducted in the COVID-19 pandemic. PAS is the final process of measuring the achievement of student learning outcomes as one of the considerations for successful knowledge acquisition in one semester. Therefore, it is necessary to have high integrity in its implementation to describe the actual learning achievement of students. This study employed a descriptive quantitative method involving teachers (n = 109), students (n = 725) and parents (n = 846) from various public and private elementary schools in Bekasi. Furthermore, survey was conducted using google form for data collection, where respondents were asked to input several statements related to the integrity of teachers, parents and students in the PAS. The data from the documents or questionnaires were analyzed using descriptive-exploratory method to draw reflective conclusions. The results showed (1) the integrity of teachers in PAS included in the low category was 15.60%, the medium was 69.72%, and high was 14.68%. (2) the integrity of students which was categorized as low was 10.89%, medium was 81.24%, and high was 7.86%. (3) the integrity of parents categorized as low was 15.60%, medium was 72.34%, and the high was 12.05%. It was concluded that teachers, students, and parents who have high integrity in PAS were far-outnumbered by those in the low or medium category. Therefore, integrity in the school and family environment should be continuously improved.